Methyl methacrylate modified chitosan: Synthesis, characterization and application in drug and gene delivery. (1st May 2019) - Jaiswal, Shefali; Dutta, P.K.; Kumar, Santosh; Koh, Joonseok; Pandey, Shambhavi
Graphical abstract: Highlights: Synthesis of methyl methacrylate modified chitosan conjugate (CSMMA) via Michael addition reaction. Physicochemical characterization of CSMMA. CSMMA has good transfection efficiency. pH-modulated drug release by CSMMA nanoparticles. Abstract: A methyl methacrylate (MMA) modified chitosan (CS) conjugate (CSMMA) has been synthesized by a green method via Michael addition reaction between CS and MMA in ethanol. The synthesized conjugate was characterized by FT-IR, 1 H NMR, X-ray diffraction spectrometry and SEM analysis. The results confirmed that CS was covalently linked to MMA yielding a highly porous framework. The uses of CSMMA were analyzed as a potential gene and drug delivery agent. CSMMA proved to be a reasonably good gene delivery agent based on transfection efficiency studies in mammalian cancer cell lines (A549, HeLa and HepG2). For drug delivery studies, nanoparticles of the CSMMA biopolymer were prepared by ionic gelation method with sodium tripolyphosphate (TPP). The prepared nanoparticles were characterized in terms of FE-SEM, DLS and zeta potential. In vitro drug release study of curcumin loaded CSMMA nanoparticles showed its maximal entrapment efficiency up to 68% and the drug release was more rapid at a pH (5.0) lower than physiological pH.